Multivariable state-space adaptive control = Adaptive Mehrgrößenzustandsregelung - Gambier, Adrián; Nazaruddin, Yul Yunazwin (Automatisierungstechnik, 2009)
The field of indirect adaptive control has been intensively studied for single input/single output (SISO) system as well as multivariable (MIMO) systems based on I/O models. State-space approaches for SISO system can also be found in the literature. Although the state-space representation is a very convenient description for multivariable systems, only few times it was applied to design indirect adaptive control systems. In this paper, the most important approaches are presented and analysed including advantages and drawbacks. Finally, the most common adaptive control schemes are illustrated with real-time results obtained from experiments carried out on a turbogenerator pilot plant.
Elektronische Reproduktion der Druckausgabe
Gesehen am 13.12.2019